2021
DOI: 10.48550/arxiv.2101.00866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is asymptotically safe inflation eternal?

Jan Chojnacki,
Julia Krajecka,
Jan H. Kwapisz
et al.

Abstract: Recently, based on swampland considerations in string theory, the (no) eternal inflation principle has been put forward. The natural question arises whether similar conditions hold in other approaches to quantum gravity. In this article, the asymptotic safety hypothesis is considered in the context of eternal inflation. As exemplary inflationary models the SU(N) Yang-Mills in the Veneziano limit and various RG-improvements of the gravitational action are studied. The existence of UV fixed point generically fla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…We now take a short break from our dimensional reduction analysis to work out the conditions for eternal inflation in general spacetime dimension d by solving the Fokker-Planck equation, generalizing the computations of [5] (see also [29][30][31][32][33][34][35][36][37][38][39]). 1 In Section 5 below, we will comment briefly on the behavior of the conditions for avoiding eternal inflation under dimensional reduction.…”
Section: Interlude: Eternal Inflation In Higher Dimensionsmentioning
confidence: 99%
“…We now take a short break from our dimensional reduction analysis to work out the conditions for eternal inflation in general spacetime dimension d by solving the Fokker-Planck equation, generalizing the computations of [5] (see also [29][30][31][32][33][34][35][36][37][38][39]). 1 In Section 5 below, we will comment briefly on the behavior of the conditions for avoiding eternal inflation under dimensional reduction.…”
Section: Interlude: Eternal Inflation In Higher Dimensionsmentioning
confidence: 99%
“…Furthermore, it seems that this is in line with the swampland conjectures and the newly proposed finiteamplitude principle [3], making the asymptotically safe quantum gravity to pick initial conditions s.t. inflation ceases to be eternal [64], see also [65,66]. From the point of view of finite action selection principle [1] they are equally good theories, resolving the black holes singularities, assuming that ghost issue is resolved in the latter case.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We observed that during inflation, the number of e-folds shows little variation across the quantum fluctuations, which is to be expected. In Figure 10,11,12 , the variations of scalar (n s ) and tensor (n h ) spectral indies and tensor-to-scalar ratio (r) against mode momenta have been shown. In Figures 13 and 14 we have shown how the results of our calculation fit the Planck 2018 data [33,34] in the n s -r plane.…”
Section: Power Spectra and Cosmological Parameters In K -Spacementioning
confidence: 97%
“…Later on and recently, the α-attractor potentials have been extensively applied [7][8][9][10][11][12] in the study of cosmological inflation and also in preheating [13] and reheating [14,15]. Also, the quintessential versions of the α-attractors have also been applied to explain the late time acceleration of the universe [16][17][18][19], as well as in the predictive study of the stage-IV galaxy surveys [20].…”
Section: Introductionmentioning
confidence: 99%